Hospital Cost Containment Efforts on the Differences between Hospital Real Rates and INA CBG's Rates for Inpatients with Pneumonia Complications at Dr. Sardjito Hospital: Upaya Pengendalian Biaya Rumah Sakit terhadap Perbedaan Tarif Riil Rumah Sakit dengan Tarif INA CBG’s Pasien Rawat Inap pada Kasus Komplikasi Pneumonia di RSUP Dr. Sardjito - Kurniawati, Indrati Dwi; Sugeng, Sugeng (Universitas Muhammadiyah Sidoarjo, 2025)
Based on preliminary studies conducted by researchers at the Medical Records and Health Information Installation of Dr. Sadrjito Hospital, it was found that the difference between the hospital’s real rates and INA-CBG’s rates for pneumonia patients from January to May of 2024 had very significant changes in rates and could cause losses to hospital agencies. The purpose of this study was to determine how efforts made by the hospital to the difference in hospital real rates and INA-CBG’s so that hospital costs are efficient. The research method used was a descriptive research method with a quantitative approach. The results of a study of 52 inpatient pneumonia cases analyzed by the researchers found that the real hospital rates were higher than the INA CBG’s rates, causing huge losses for the hospital. The factor that causes the difference in real hospital rates is the lack of JKN claim guarantee costs, while cases of penumonia with complications have a long stay (LOS) of more than 12 days with high action costs, then the hospital must make cost control efforts by implementing standardized services so that hospital costs become more efficient and not the occurrence of higher hospital riil rates than INA-CBG’s.Suggestions for the hospital to reduce losses are to evaluate the calculation of unit costs in each inpatient unit service, monitor and evaluate claims for inpatient service costs through monitoring the coding process, verification and implementing clinical pathways in all services.